PENINGKATAN HASIL BELAJAR SKI MENGGUNAKAN MEDIA AUDIO VISUAL KLS VIIB DI MTS TARBIYAH ISLAMIYAH MAYANG - Yusria; Rama Trian Caetheby; Septiana Indriani Br Gultom; Muna Azkia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low effectiveness of learning Islamic Cultural History (SKI) in class VII B MTs Tarbiyah Islamiyah Simpang III Sipin, Jambi. This is due to the limited use of learning media, which only uses the blackboard. To overcome these problems, this study applied audio-visual media as an innovation in the learning process. This study used the Classroom Action Research (PTK) method which was carried out in two cycles with 15 students as research subjects. Data collection techniques were carried out through observation, pretest, posttest, and documentation. The results showed an increase in teacher and student activities and an increase in learning outcomes. Learning completeness increased from 20% in the pre-cycle to 80% in cycle I, and 86.67% in cycle II. The use of audio visual media proved effective in improving SKI learning outcomes in class VII B MTs Tarbiyah Islamiyah.